Quality of life in university students with overweight and obesity: Differences by sex - Jesús Alberto García García; Julio Cufarfán López (Interacciones)
Introduction: The objective of this article is to show the relation between the quality of life, overweight and obesity, and to compare if there are significant differences by gender. Methodology: The SF-36v2 questionnaire was used to measure the functional health and wellness from eight dimensions: physical function, physical role, body pain, general health, vitality, social function, emotional role and mental health. The study is quantitative with a traversal, observational and prospective design. The statistical techniques that were used to the data analysis was the Pearson relation coefficient and the t test to independent samples. The d of Cohen was used to obtain the magnitude of the effect. The sample was selected from a non-probabilistic sample by convenience; the total of participants was of 320. Results: Significant statistic differences were found in two of the dimensions, with a small magnitude of the effect, less than a standard deviation. Conclusion: Women feel more energy and vitality than men, whom sometimes are more affected by the physical or emotional health problems that interfere in their social life.